Taf'il Daur al-Ansyițah al-Madrasiyyah li Tanmiyati al-Mahārāt al-Lughawiyyah (Ma'had Dārussalam Gontor li Tarbiyah al-Islāmiyyah al-Hadīśah Namūdażan) - Abdul Hafidz Zaid (LISANUDHAD: JURNAL BAHASA, PEMBELAJARAN DAN SASTRA ARAB, 2017)
Abstract            The Arabic language has become remarkably popular in recent times with the increasing number of Muslims in all countries of the world. Furthermore, the huge demand to learn it from non-Arab in Arab countries and non-Arab educational institutions make the scientists in this area of expertise think about the means to facilitate the students’ acquisition of Arabic language. It is believed that the most important means is to create a linguistic environment with all its activities and language acquisition programs. Islamic Boarding School of Darussalam Gontor (Pondok Modern Darussalam Gontor) was fully aware of the need to create a linguistic environment when the direct method was in sight at the turn of the century. It was used by Islamic Boarding School of Darussalam Gontor as a basic method of teaching Arabic and this iinstitution was making efforts to create an encouraging atmosphere for all its students to learn Arabic. Through various language activities and games, this institution has organized competitions in speech, theatre, debate and other competitions in Arabic in addition to forming a section in the student organization that manages the language activities within this institution. For this purpose, Islamic Boarding School of Darussalam Gontor has developed a special approach to make it easier for its students to acquire Arabic language. It is noteworthy that this institution has not relied on modern methods and advanced technology in its education. Rather, it relied on the linguistic environment which cover activities to improve it.Keywords: Linguistic environment, Islamic boarding school of Darussalam Gontor, Arabic teaching, direct method, Acquisition of foreign language.                         تفعيل دور الأنشطة المدرسية لتنمية المهارات اللغوية(معهد دار السلام كونتور للتربية الإسلامية الحديثة نموذجًا)بقلم: د. عبدالحافظ زيدجامعة دار السلام كونتور ملخصانتشرت اللغة العربية بشكل لافت للنظر في الآونة الأخيرة مع تزايد عدد المسلمين في جميع دول العالم، وكان الإقبال على تعلُّمها من غير أبنائها في المؤسسات التعليمية العربية وغير العربية شديدًا؛ مما يجعل العلماء في هذا المجال يفكرون في الوسائل التي تسهل للدارسين اكتسابَها، ولعلَّ أهم تلك الوسائل هو تكوين البيئة اللغوية بكلِّ ما فيها من الأنشطة والبرامج اللغوية. كان معهد دار السلام كونتور على وعي تام بضرورة تكوين البيئة اللغوية، فعندما لاحت الطريقة المباشرة في الأفق مع مطلع القرن الماضي، استخدمها المعهد بكونها طريقةً أساسية في تعليم اللغة العربية و بذل معهد دار السلام كونتور جهودَه من أجلِ خلق جوٍّ مشجِّع لجميع طلابه لتعلم اللغة العربية، من خلال أنشطة وألعاب لغويَّة عديدة، فقد نظم المعهد مسابقاتٍ في الخطابة والمسرحية والمناظرة وغيرها من المسابقات باللغة العربية، بالإضافة إلى تشكيل قسم في منظمة الطلاب يتولَّى إدارة الأنشطة اللغويَّة داخل حرم المعهد. فقد وضع معهد دار السلام كونتور من أجل ذلك منهجًا خاصًّا؛ حتى يسهِّل على طلابه اكتسابَها، ومن الملاحظ أن هذه المؤسسة التعليمية لم تعتمد على الوسائل الحديثة والتكنولوجيا المتطوِّرة في تعليمها بقدر اعتمادِها على البيئة اللغوية بما فيها من الأنشطة المتنوعة.الكلمات الرئيسية: البيئة اللغوية، معهد دار السلام كونتور، تعليم اللغة العربية، المنهج المباشر، اكتساب اللغة الأجنية.